The too-late trail : a Ralph Compton western - Compton, Ralph; Mayo, Matthew P. (Compton, Ralph. Trail drive series., 2021)
Young Mitchell Newland, losing everything during a cattle drive, discovers just how many times a man's luck can hold out as he fights to reclaim what's his or die trying.